Multifunctional Intelligent Helmet to Enhanced Safety and Comfort of Laborers in the Mining Industry - Harshal Ambadas Durge; Vijay Mahadeo Mane; Arjun Jaggi; Preetish Kakkar (Advances in Technology Innovation, 2025)
This study aims to enhance miner safety through real-time monitoring and emergency responses. To achieve this, a multi-functional mining helmet (MFMH) is designed with location tracking via a global system for mobile communications (GSM) and global positioning system (GPS), hazardous gas detection, lighting, and temperature regulation, along with vibration-based alerts for emergency notification. The helmet is tested in simulated mining environments to assess its performance. The system successfully detected hazardous gases at concentrations of 41.23 ppm, triggered automatic lighting when luminosity dropped below 35 lux, and maintained internal temperatures between 26 ℃ and 27 ℃, demonstrating its effectiveness in safety.